Office Aplication Training ( Ms Office ) For The Community Of Holtekamp Village - Fegie Y Wattimena; Reni Koibur; Andrijanni (International Journal Of Community Service, 2022)
Based on the survey results, it is concluded that there was a lack of knowledge and skills of the Holtekamp village community, especially young people, church administrators and village officials in operating Office Applications (MS Office). This training aimed to provide knowledge and skills about the importance of mastering Office Applications (MS Office), namely word processing (MS Word), Spreadsheet data processing (MS Excel) and MS Power Point for presentations. The methods used in this training was mentoring method with lecture techniques to explain theory and practice directly on a computer that has MS Office installed. The training was carried out for 7 days with 3 hours of meetings. The number of participants who participated in the training was 23 people. The result of this training is that the level of knowledge and skills of the trainees increased from the Pre Test results of 34.42% to the Post test results of 90.7%